Association of Endolymphatic Hydrops and Otosclerosis. (2nd September 2014) - Terao, Kyoichi; Doi, Katumi; Cureoglu, Sebahattin; Paparella, Michael M.
Abstract : Objectives: Study the correlations of endolymphatic hydrops and vestibular symptoms with otosclerotic foci. Methods: Comparative study of human temporal bone histopathology. In addition to areas of the stria vascularis and spiral ligament and the presence of endolymphatic hydrops, locations and degree of endosteal involvement and size of otosclerotic foci were examined in 132 temporal bones from 95 subjects with otosclerosis. The degree of endolymphatic hydrops was classified as mild, moderate and severe. Results: Fifty temporal bones (37.9%) from 39 subjects with otosclerosis had a histopathological finding of endolymphatic hydrops. The most common location of endosteal involvement was the endosteum of the perilymphatic space of the vestibule. In terms of locations and degree of endosteal involvement and size of otosclerotic foci, there was a significant increase in subjects with otosclerosis with endolymphatic hydrops compared with subjects with otosclerosis without endolymphatic hydrops. Twenty five subjects (26.3%) had a documented history of vestibular symptoms in patients with otosclerosis. In addition to the presence of endolymphatic hydrops, locations and degree of endosteal involvement and size of otosclerotic foci were significantly greater in subjects with otosclerosis with vestibular symptoms compared with subjects with otosclerosis without vestibular symptoms. Conclusions: Endolymphatic hydrops is more common than previously realized in patients with otoslerosis. The common association of these 2 otologic conditions encourages researchers. Clinicians should keep in mind the common association of these 2 otologic conditions when encountering a patient with either of these conditions.